Cannabidiol Acts at 5-HT1A Receptors in the Human Brain: Relevance for Treating Temporal Lobe Epilepsy - Martínez-Aguirre, Christopher; Carmona-Cruz, Francia; Velasco, Ana Luisa; Velasco, Francisco; Aguado-Carrillo, Gustavo; Cuéllar-Herrera, Manola; Rocha, Luisa (Frontiers in Behavioral Neuroscience, 2020)
Experimental evidence indicates that cannabidiol (CBD) induces anxiolytic and antiepileptic effects through the activation of 5-HT1A receptors. These receptors are coupled to Gi/o-proteins and induce inhibitory effects. At present, the interaction of CBD with 5-HT1A receptors in the human brain is unknown. The aim of this study focused on evaluating the interaction between CBD and 5-HT1A receptors in cell membranes obtained from the hippocampus and temporal neocortex of autopsies and patients with drug-resistant mesial temporal lobe epilepsy (DR-MTLE). Cell membranes were isolated from the hippocampus and temporal neocortex of a group of patients with DR-MTLE who were submitted to epilepsy surgery (n = 11) and from a group autopsies (n = 11). The [3H]-8-OH-DPAT binding assay was used to determine the pharmacological interaction of CBD with 5-HT1A receptors. The [35S]-GTPS assay was used to investigate the CBD-induced activation of Gi/o proteins through its action on 5-HT1A receptors. The CBD affinity (pKi) for 5-HT1A receptors was similar for autopsies and patients with DR-MTLE (hippocampus: 4.29 and 4.47, respectively; temporal neocortex: 4.67 and 4.74, respectively). Concerning the [35S]-GTPS assay, no statistically significant changes were observed for both hippocampal and neocortical tissue (p > 0.05) at low CBD concentrations (1 pM to 10 µM). In contrast, at high concentrations (100 µM), CBD reduced the constitutive activity of Gi/o proteins of autopsies and DR-MTLE patients (hippocampus: 39.2% and 39.6%, respectively; temporal neocortex: 35.2% and 24.4%, respectively). These changes were partially reversed in the presence of WAY-100635, an antagonist of 5-HT1A receptors, in the autopsy group (hippocampus, 59.8%, p<0.0001; temporal neocortex, 71.5%, p <0.0001) and the group of patients with DR-MTLE (hippocampus, 53.7%, p<0.0001; temporal neocortex, 68.5%, p<0.001). Our results show that CBD interacts with human 5-HT1A receptors of the hippocampus and temporal neocortex. At low concentrations, the effect of CBD upon Gi/o protein activation is limited. However, at high concentrations, CBD acts as an inverse agonist of 5-HT1A receptors. This effect could modify neuronal excitation and epileptic seizures in patients with DR-MTLE.